171k views
0 votes
Let f(x) = x2 - 1 and g(x) = 2x - 3. Find the new function and write it in simplest form

f+g
a.
-x² + 2x - 2
b. x2 - 2x + 2
x² + 2x - 4
d. 2x3 - 3x2 - 2x + 3
Please select the best answer from the choices provided
A
B
С
D

Let f(x) = x2 - 1 and g(x) = 2x - 3. Find the new function and write it in simplest-example-1

2 Answers

2 votes

Answer:

Explanation:

User Joel Bender
by
4.2k points
1 vote

Answer:

Option C is the correct answer


{x}^(2) + 2x - 4

Explanation:


f(x) = {x}^(2) - 1 \\ g(x) = 2x - 3 \\ (f + g)(x) = f(x) + g(x) \\ (f + g)(x) = {x}^(2) - 1 + 2x - 3 \\ \purple{ \boxed{ \bold{ (f + g)(x) = {x}^(2) + 2x - 4}}}

User Muzammil Naseer
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.